Understanding COVID-19 Vaccination Uptake: Insights from a Coastal Community in Northern Mindanao - Araune, Paolo (Alta Dharma Publisher, 2024)
Background & Aim: The rapid spread of COVID-19 caused widespread disruption and highlighted the urgent need for vaccination strategies. Despite significant efforts, some communities, including one in coastal Northern Mindanao, faced challenges in achieving vaccination targets. This study aimed to identify barriers to COVID-19 vaccination uptake and their impact on behavioral practices in the community. Methods & Materials: This quantitative study employed correlational and descriptive statistical analyses to examine variables. Surveys were distributed to households and the barangay health center, utilizing stratified random sampling to ensure unbiased representation based on age. Participants aged 20-64, eligible for COVID-19 vaccination, were surveyed. Using the Cochran formula, a sample size of approximately 372 residents was determined. Results: No significant differences were found in respondents' agreement levels on COVID-19 vaccination behavioral practices across age groups. However, significant differences were observed based on educational attainment and gender. College graduates showed higher agreement levels in attitude and behavioral intention. Female respondents exhibited higher agreement in attitude and perceived behavioral control, while male respondents had higher agreement on subjective norms. No significant differences were found based on religion. Conclusion: Knowledge positively correlated with agreement on vaccination practices, underscoring the importance of education in addressing vaccine hesitancy. While religious affiliation influenced attitudes, individual beliefs within religious groups varied. These findings highlight the multifaceted factors influencing COVID-19 vaccination acceptance and suggest targeted interventions to address specific demographic disparities.